Method for recycling cellulose / polyester blended fabric through one-bath process and preparing composite fiber
By using LiCl/solvent system to swell at high temperature and dissolve cellulose/polyester blended textiles at low temperatures, combined with the solution spinning process, the problem of difficult cellulose and polyester recycling in the prior art is solved, and efficient and simple recycling and reuse of composite fibers is achieved.
Patent Information
- Application Number
- CN202510210454.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-05-06
- Estimated Expiration
- 2045-02-25
AI Technical Summary
The prior art is difficult to effectively recycle and reuse cellulose/polyester blended textiles, and the existing methods are complex and have many side reactions, making it difficult to effectively separate and utilize cellulose and polyester.
The mixed solvent system of LiCl/solvent is used to swell and dissolve the cellulose/polyester blended textile at high temperature. Through the high-temperature swelling and low-temperature dissolution, a uniform mixed solution is formed, and the regenerated composite fibers are then prepared by the solution spinning process.
Effective recycling and reuse of cellulose and polyester is achieved, the recycling process is simplified, and composite fibers with excellent mechanical properties are obtained, reducing resource waste and environmental pollution.
Smart Images

Figure BDA0005285869330000051 
Figure BDA0005285869330000061 
Figure BDA0005285869330000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric recycling and reuse, and in particular to a method for recycling cellulose / polyester blended fabrics by a one-bath method and preparing composite fibers. Background Art
[0002] Polyester is widely used in clothing and household textiles due to its wrinkle resistance, wear resistance, moisture absorption and quick drying. It is often used to make shirts, pants and sportswear, etc. It is one of the most widely used synthetic fibers in the clothing industry. Polylactic acid is a biodegradable and environmentally friendly fiber. In the past two years, driven by environmental protection policies, the market demand has continued to grow. In the field of clothing, it is often used in yoga clothes, cycling clothes, etc. due to its good moisture absorption and perspiration and UV protection functions. Cellulose fiber is often used to make daily clothing, underwear and bedding due to its softness and hygroscopicity, and is also widely used in industries such as filter materials and medical gauze. Polyester and cellulose fibers occupy an important position in both clothing and industrial fields. Although the proportion of polylactic acid fiber is relatively small, its growth rate is rapid. In view of the current situation of increasing resource scarcity, recycling polyester, polylactic acid and cellulose fibers can reduce the accumulation of waste textiles, and can also effectively reduce deforestation and reduce dependence on natural resources, thereby protecting the ecological environment, and has significant environmental protection and resource utilization value.
[0003] The recycling methods of polyester (including polyester and polylactic acid) mainly include physical recycling, chemical recycling and chemical-physical combined recycling. Among them, the chemical recycling method is widely used because it can obtain high-quality polyester fibers and has good environmental benefits. The chemical recycling method uses chemical reactions to depolymerize waste polyester materials into polymer monomers or polymer intermediates, producing products with relatively high purity, clear structure and relatively few types. The process involves the degradation of polymers and the breaking of chemical bonds under specific conditions. The ester bonds in polyesters react with alcohols, amines, heat or water under specific conditions to efficiently degrade and generate all or part of the constituent structural units of the polymer. Although alcoholysis and hydrolysis methods can efficiently degrade polyester fibers and obtain monomers or monomer fragments with higher purity, these methods require the use of excess reaction reagents, and the excess unreacted parts need to be removed after the reaction is completed. The process is relatively complicated and the economic effect is low. The recycling methods of cellulose fibers mainly include physical recycling and chemical recycling. Physical recycling is to use mechanical means to decompose waste textiles into short fibers and fragments, and then make regenerated cellulose fibers through processes such as washing, combing and respinning. The process is simple and the cost is low, but the quality of the recycled fibers is low. Chemical recycling uses chemical reagents or solvents to dissolve the cellulose in waste textiles. It mainly uses technical routes such as NaOH / urea water solvent system, NMMO solvent method and ion solution to dissolve it and then make cellulose products through spinning and other processes. Although the NaOH / urea water solvent system method has many advantages, the system will produce high-salinity wastewater during the treatment process, which increases the difficulty and cost of wastewater treatment. In addition, the stability and repeatability of the system are low. The NMMO system also faces the problem of wastewater treatment, and its process is relatively cumbersome and energy-intensive. In contrast, ionic solutions have significant advantages in chemical recycling due to their excellent solubility, good chemical properties and thermal stability, as well as environmentally friendly and recyclable characteristics.
[0004] In real life, most waste textiles are composed of blended fibers, among which cellulose / polyester blended fibers are more common. Although the components of cellulose or polyester fibers can be easily recycled, on the one hand, the existing technologies mostly use physical or chemical methods to separate cellulose and polyester fibers, and then treat them separately to achieve their recycling and reuse. Such methods usually involve complex processing processes and have many side reactions. There are few existing technologies that directly dissolve cellulose / polyester blended fabrics and then re-spin to prepare composite fibers; on the other hand, due to the different properties of cellulose and polyester, existing methods are usually difficult to achieve effective separation and utilization of the two. Even if the two can be well separated by combining physical and chemical methods, the properties of the separated fibers will be affected, resulting in poor mechanical properties of the prepared blended fabric. Therefore, it is particularly necessary to develop a new method that can recycle cellulose and polyester fibers in one step and upgrade waste fabrics into high value-added products. Summary of the invention
[0005] In view of the above-mentioned problems, the present invention proposes a method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process, wherein waste cellulose / polyester blended fabrics are dissolved in LiCl / solvent, and high-temperature swelling and low-temperature dissolution methods are combined to promote the dissolution of cellulose and polyester to obtain a uniform mixed solution, and then the mixed solution is converted into regenerated cellulose / polyester composite fibers by a solution spinning method. This method can not only simplify the recycling method, but also obtain composite fibers with excellent mechanical properties.
[0006] In view of the above purpose, the present invention first discloses a method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process, comprising the following steps:
[0007] (1) activating, washing and drying the cellulose / polyester blended fabric to obtain an activated blended fabric;
[0008] (2) mixing the activated blended fabric obtained in step (1) with a solvent, and performing a first stage of stirring at a high temperature to dissolve the polyester component and simultaneously complete the swelling of the cellulose component; adding LiCl to the obtained mixed system to form a LiCl / solvent mixed solvent system with the solvent, and continuing to perform a second stage of stirring at a high temperature;
[0009] (3) transferring the reaction system obtained in step (2) to a lower temperature environment and performing a third stage of stirring to complete the dissolution of the cellulose component and form a uniform mixed solution;
[0010] (4) preparing regenerated composite fibers by a solution spinning process using the mixed solution obtained in step (3);
[0011] Alternatively, (1) activating, washing and drying the cellulose / polyester blended fabric to obtain an activated blended fabric;
[0012] (2) mixing the activated blended fabric obtained in step (1) with a LiCl / solvent mixed solvent system, and performing a first stage of stirring at a high temperature to dissolve the polyester component and simultaneously complete swelling of the cellulose component; and continuing to perform a second stage of stirring at a high temperature;
[0013] (3) transferring the reaction system obtained in step (2) to a lower temperature environment and performing a third stage of stirring to complete the dissolution of the cellulose component and form a uniform mixed solution;
[0014] (4) The mixed solution obtained in step (3) is subjected to a solution spinning process to prepare a composite fiber.
[0015] In one embodiment of the present invention, the cellulose / polyester blended fabric in step (1) is a cellulose / polyester blended fabric or a cellulose / polylactic acid fiber blended fabric.
[0016] In one embodiment of the present invention, the mass fraction of cellulose in the cellulose / polyester blended fabric in step (1) is 35-99%.
[0017] In one embodiment of the present invention, the activation in step (1) refers to activation using a sodium hydroxide aqueous solution with a mass fraction of 5 to 20%, an activation temperature of 20 to 80° C., preferably 40 to 60° C., and an activation time of 1 to 5 hours, preferably 2 to 4 hours.
[0018] In one embodiment of the present invention, the cleaning in step (1) refers to washing with deionized water and a solvent for 3 to 5 times respectively until no sodium hydroxide remains, and the solvent includes at least one of dimethylformamide (DMF), dimethylacetamide (DMAc) and dimethyl sulfoxide (DMSO), and the drying temperature is 40 to 50° C. and the drying time is 2 to 5 hours.
[0019] In one embodiment of the present invention, the solvent in step (2) comprises at least one of DMF, DMAc and DMSO.
[0020] In one embodiment of the present invention, the mass ratio of the activated blended fabric to the LiCl / solvent mixed solvent system in step (2) is 1 to 10:100, and the mass concentration of LiCl in the LiCl / solvent mixed solvent system is 2 to 10%.
[0021] In one embodiment of the present invention, the high temperature in step (2) is 90-150° C., and the stirring speed is 30-600 r / min.
[0022] In one embodiment of the present invention, in step (2), the stirring time of the first stage is 1 to 2 hours, and the stirring time of the second stage is 1 to 3 hours.
[0023] In one embodiment of the present invention, in step (3), the relatively low temperature environment refers to an environment with a temperature of 20 to 60° C., the stirring time of the third stage is 1 to 3 hours, and the stirring speed is 30 to 600 r / min.
[0024] In one embodiment of the present invention, the spinning process described in step (4) refers to wet spinning or dry-jet wet spinning, and the breaking strength of the obtained regenerated composite fiber is 1.0-3.0 cN / dtex and the breaking elongation is 5-15%.
[0025] In one embodiment of the present invention, during the solution spinning process in step (4), the temperature of the spinning solution is 80 to 120° C., and the extrusion pressure is 1 to 5 kg / cm 2 , extrusion speed is 1 to 3 m / min; spinneret diameter is 0.2 μm, coagulation bath is carried out in deionized water at 20 to 40°C; air gap is 0-1 cm, total draft multiple is 1 to 5 times, drying temperature is 30 to 50°C, winding speed is 1 to 15 m / min, preferably 1 to 5 m / min.
[0026] The invention also provides a composite fiber prepared according to the method.
[0027] Beneficial effects:
[0028] 1. The present invention uses a mixed solvent system of LiCl / solvent as an ion solution, and swells and dissolves the cellulose and polyester in the cellulose / polyester blended fabric in steps. By optimizing the dissolution system and reaction conditions, it is achieved that a single ion solvent is used to simultaneously dissolve two different components of cellulose and polyester. The obtained solution has uniform texture and high stability. The solution spinning process can be directly used to obtain regenerated composite fibers, and the fibers have good mechanical properties.
[0029] 2. The components of the composite fiber recovered in the present invention are regenerated cellulose and polyester. Cellulose has good hydrophilicity and can improve the hydrophilicity of the composite fiber. The polyester fiber provides a certain strength for the composite fiber.
[0030] 3. The process conditions adopted by this patent do not require the use of strong acids or strong bases. The dissolution system used has low toxicity and the pretreatment process is simple, which effectively improves the recycling efficiency of waste blended fabrics. The entire recycling process is carried out under mild conditions (90-150°C, normal pressure) and no side reactions occur, which simplifies the recycling process and reduces the complexity of recycling blended fabrics.
[0031] 4. The present invention not only realizes the recovery of all components of waste blended fabrics, but also avoids the waste of resources and environmental pollution caused by incineration or landfill in traditional treatment methods, and converts waste textiles into high-value recycled composite fibers, significantly improving the economic effect.
[0032] 5. The method of the present invention can achieve effective dissolution of cellulose and polyester in cellulose / polyester blended fabrics. The obtained solution has uniform texture. The dissolved solution is spun to obtain composite fibers with good mechanical properties. The composite fibers prepared by the method of the present invention have a breaking strength of up to 2.7 cN / dtex and an elongation at break of up to 13.5%. DETAILED DESCRIPTION
[0033] The present invention is described in detail below with reference to specific examples.
[0034] Test method:
[0035] The elongation at break and the breaking strength of the composite fiber are tested according to the method in standard GB / T 14337, wherein the fiber is in a dry state, the sample stretching length is 10 mm, the stretching speed is 5 mm / min, the temperature is room temperature, and the humidity is 65%±2%.
[0036] Example 1
[0037] A method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process comprises the following steps:
[0038] 1) Mechanically crushing a cellulose / polylactic acid fabric (35:65), then treating it with a 17% by mass NaOH aqueous solution at 50° C. for 3 h, washing it with deionized water for 3 to 5 times, drying it at 50° C. for 3 to 5 h until it is dry, then washing it with a DMAc solvent for 2 to 3 times and drying it at 50° C. for 3 to 5 h until it is dry, to obtain a fabric powder;
[0039] 2) taking 3 parts of the fabric powder obtained in step 1), firstly putting it into 92 parts of DMAc solvent, and carrying out the first stage stirring at 90° C., the stirring time is 1 h, and the stirring speed is 300 r / min, so that the polylactic acid is dissolved and the cellulose is swollen at the same time;
[0040] 3) adding 8 parts of LiCl to the mixed system obtained in step 2) so that the mass fraction of LiCl in the LiCl / DMAc ion solution system is 8%, continuing the second stage stirring at 90° C. for 2 h at a stirring speed of 100 r / min, then transferring the system to 40° C., and carrying out the third stage stirring under this condition for 2 h at a stirring speed of 50 r / min to obtain a cellulose / polylactic acid / LiCl / DMAc solution with a uniform texture;
[0041] 4) The regenerated cellulose / polylactic acid composite fiber was obtained by wet spinning. During the wet spinning process, the temperature of the spinning solution was 100°C and the extrusion pressure was 3 kg / cm 2 , extrusion speed is 2m / min; spinneret diameter is 0.2μm, coagulation bath is carried out in deionized water at 35℃; total drafting multiple is 2 times, drying temperature is 50℃, and winding speed is 4m / min.
[0042] Example 2
[0043] The difference between Example 2 and Example 1 is that the temperature of the first stage in step 2) and the second stage in step 3) is replaced with 110°C.
[0044] Example 3
[0045] The difference between Example 3 and Example 1 is that the temperature of the first stage in step 2) and the second stage in step 3) is replaced with 130°C.
[0046] Example 4
[0047] The difference between Example 4 and Example 1 is that the temperature of the first stage in step 2) and the second stage in step 3) is replaced with 150°C.
[0048] Example 5
[0049] The difference between Example 5 and Example 4 is that step 2) is omitted, and 1 portion of fabric powder is directly added into a LiCl / DMAc ion solution system with a LiCl mass fraction of 8% and stirred at high temperature for 3 hours.
[0050] The dissolution of the fiber in the cellulose / polylactic acid / LiCl / DMAc solution obtained in step 3) is observed, as shown in Table 1. It can be seen from Table 1 that different high-temperature stirring temperatures are set in Examples 1 to 4, and the cellulose / polylactic acid blended fabric can be dissolved into a uniform and stable solution within 90 to 150°C. In Example 5, the cellulose / polyester blended fabric is directly mixed with a mixed solvent system consisting of LiCl / solvent for high-temperature stirring and low-temperature stirring, and the obtained solution has uniform and stable properties, which is almost the same as the solutions obtained in Examples 1 to 4. It can be seen from the tensile performance data of the composite fiber obtained in step 4) that as the temperature increases, the fiber macromolecular chain is straighter, the flexibility is better, and it is more suitable for spinning; however, as the temperature rises to 150°C, the cellulose will be degraded due to the high temperature, resulting in a decrease in fiber performance.
[0051] Table 1 Dissolution and fiber properties of fabrics of Examples 1 to 5 after three-stage stirring
[0052]
[0053] Example 6
[0054] A method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process comprises the following steps:
[0055] 1) Mechanically crushing a cellulose / polylactic acid fabric (35:65), then treating it with a 17% by mass NaOH aqueous solution at 50° C. for 3 h, washing it with deionized water for 3 to 5 times, drying it at 50° C. for 3 to 5 h until it is dry, then washing it with a DMAc solvent for 2 to 3 times and drying it at 50° C. for 3 to 5 h until it is dry, to obtain a fabric powder;
[0056] 2) taking 3 parts of the fabric powder obtained in step 1), firstly putting it into 90 parts of DMAc solvent, and carrying out the first stage stirring at 110° C., the stirring time is 1 h, and the stirring speed is 300 r / min, so that the polylactic acid is dissolved and the cellulose is swollen at the same time;
[0057] 3) adding 10 parts of LiCl to the mixed system obtained in step 2) so that the mass fraction of LiCl in the LiCl / DMAc ion solution system is 10%, continuing the second stage stirring at 110° C. for 1.5 hours at a stirring speed of 100 r / min, then transferring the system to 40° C., and carrying out the third stage stirring under this condition for 2 hours at a stirring speed of 50 r / min, to obtain a cellulose / polylactic acid / LiCl / DMAc solution with a uniform texture;
[0058] 4) The regenerated cellulose / polylactic acid composite fiber was obtained by wet spinning. During the wet spinning process, the temperature of the spinning solution was 100°C and the extrusion pressure was 3 kg / cm 2 , extrusion speed is 2m / min; spinneret diameter is 0.2μm, coagulation bath is carried out in deionized water at 35℃; total drafting multiple is 2 times, drying temperature is 50℃, and winding speed is 4m / min.
[0059] Example 7
[0060] The difference between Example 7 and Example 6 is that the stirring time of the second stage in step 3) is replaced with 2 hours.
[0061] Example 8
[0062] The difference between Example 8 and Example 6 is that the stirring time of the second stage in step 3) is replaced with 2.5 h.
[0063] Example 9
[0064] The difference between Example 9 and Example 6 is that the stirring time of the second stage in step 3) is replaced with 3 hours.
[0065] Example 10
[0066] The difference between Example 10 and Example 9 is that step 2) is omitted, and 3 parts of fabric powder are directly added into a LiCl / DMAc ion solution system with a LiCl mass fraction of 10% and stirred at high temperature for 4 hours.
[0067] The dissolution of the fiber in the cellulose / polylactic acid / LiCl / DMAc solution obtained in step 3) is observed, as shown in Table 2. It can be seen from Table 2 that Examples 6 to 9 set different second-stage high-temperature stirring times, and the cellulose / polylactic acid blended fabric can be dissolved into a uniform and stable solution within 1.5 to 3 hours. Example 10 is to directly mix the cellulose / polyester blended fabric with a mixed solvent system composed of LiCl / solvent for high-temperature stirring and low-temperature stirring, and the obtained solution has uniform and stable properties, which is almost the same as the solution obtained in Examples 6 to 9. From the data of the tensile properties of the composite fiber obtained in step 4), it can be seen that with the increase of the second-stage dissolution time, the solution dissolves more evenly, and the composite fiber obtained by spinning has higher performance. However, the longer the time, the more serious the degradation, and the fiber performance decreases.
[0068] Table 2 Dissolution and fiber properties of fabrics of Examples 6 to 10 after three-stage stirring
[0069]
[0070]
[0071] Embodiment 11
[0072] A method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process comprises the following steps:
[0073] 1) Mechanically crushing a cellulose / polylactic acid fabric (35:65), then treating it with a 17% by mass NaOH aqueous solution at 60° C. for 2.5 h, washing it with deionized water for 3 to 5 times, drying it at 50° C. for 3 to 5 h until it is dry, then washing it with a DMF solvent for 2 to 3 times and drying it at 50° C. for 3 to 5 h until it is dry, to obtain a fabric powder;
[0074] 2) taking 1 part of the fabric powder obtained in step 1), firstly putting it into 90 parts of DMF solvent, and carrying out the first stage stirring at 110° C., the stirring time is 1.5 h, and the stirring speed is 300 r / min, so that the polylactic acid is dissolved and the cellulose is swollen at the same time;
[0075] 3) adding 10 parts of LiCl to the mixed system obtained in step 2) so that the mass fraction of LiCl in the LiCl / DMF ion solution system is 10%, continuing the second stage stirring at 110° C. for 2 h at a stirring speed of 100 r / min, then transferring the system to 50° C., and carrying out the third stage stirring under this condition for 1.5 h at a stirring speed of 50 r / min, to obtain a cellulose / polylactic acid / LiCl / DMF solution with uniform texture;
[0076] 4) The regenerated cellulose / polylactic acid composite fiber was obtained by wet spinning. During the wet spinning process, the temperature of the spinning solution was 100°C and the extrusion pressure was 3 kg / cm 2 , extrusion speed is 2m / min; spinneret diameter is 0.2μm, coagulation bath is carried out in deionized water at 35℃; total drafting multiple is 2 times, drying temperature is 50℃, and winding speed is 4m / min.
[0077] Example 12
[0078] The difference between Example 12 and Example 11 is that the weight parts of the fabric powder in step 2) are replaced with 3 parts.
[0079] Example 13
[0080] The difference between Example 13 and Example 11 is that the weight parts of the fabric powder in step 2) are replaced with 5 parts.
[0081] Embodiment 14
[0082] The difference between Example 14 and Example 11 is that the weight parts of the fabric powder in step 2) are replaced with 7 parts.
[0083] Embodiment 15
[0084] The difference between Example 15 and Example 11 is that the weight parts of the fabric powder in step 2) are replaced by 9 parts.
[0085] Example 16
[0086] The difference between Example 16 and Example 15 is that step 2) is omitted, and 9 parts of fabric powder are directly added into a LiCl / DMF ion solution system with a LiCl mass fraction of 10% and stirred at high temperature for 3.5 hours.
[0087] The dissolution of the fiber in the cellulose / polylactic acid / LiCl / DMF solution obtained in step 3) is observed, as shown in Table 3. It can be seen from Table 3 that different fabric mass ratios are set in Examples 11 to 15, and the cellulose / polylactic acid blended fabric can be dissolved into a uniform and stable solution within 1 to 9:100. In Example 16, the cellulose / polyester blended fabric is directly mixed with a mixed solvent system consisting of LiCl / solvent and stirred at high temperature and low temperature. The obtained solution has uniform and stable properties, which is almost the same as the solutions obtained in Examples 11 to 15. It can be seen from the tensile performance data of the composite fiber obtained in step 4) that as the amount of fabric added increases, the solution dissolves more uniformly, and the composite fiber obtained by spinning has higher performance.
[0088] Table 3 Dissolution and fiber properties of fabrics of Examples 11 to 16 after stirring in the third stage
[0089]
[0090] Embodiment 17
[0091] A method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process comprises the following steps:
[0092] 1) cellulose / polyester fabric (65:35) is first mechanically crushed, then treated with a 17% by mass NaOH aqueous solution at 70° C. for 2 h, washed with deionized water 3 to 5 times, dried at 50° C. for 3 to 5 h until dry, then washed with DMSO solvent 2 to 3 times and dried at 50° C. for 3 to 5 h until dry, to obtain fabric powder;
[0093] 2) taking 3 parts of the fabric powder obtained in step 1), firstly put it into 90 parts of DMSO solvent, and carry out the first stage of stirring at 110° C. for 1 hour, so that the polyester is dissolved and the cellulose is swollen at the same time;
[0094] 3) adding 10 parts of LiCl to the mixed system obtained in step 2) so that the mass fraction of LiCl in the LiCl / DMSO ion solution system is 10%, continuing the second stage stirring at 110° C. for 1.5 hours at a stirring speed of 300 r / min, then transferring the system to 30° C., and carrying out the third stage stirring under this condition for 1.5 hours at a stirring speed of 500 r / min, to obtain a cellulose / polyester / LiCl / solvent solution with uniform texture;
[0095] 4) The regenerated cellulose / polylactic acid composite fiber was obtained by dry-jet wet spinning. During the spinning process, the spinning solution temperature was 100°C and the extrusion pressure was 3 kg / cm 2 , extrusion speed is 2m / min, spinneret diameter is 0.2μm, air gap is 1cm, coagulation bath is carried out in 35℃ deionized water; total draft multiple is 5 times, drying temperature is 50℃, winding speed is 10m / min.
[0096] Embodiment 18
[0097] A method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process comprises the following steps:
[0098] 1) cellulose / polyester fabric (65:35) is first mechanically crushed, then treated with a 17% by mass NaOH aqueous solution at 70° C. for 2 h, washed with deionized water 3 to 5 times, dried at 50° C. for 3 to 5 h until dry, then washed with DMSO solvent 2 to 3 times and dried at 50° C. for 3 to 5 h until dry, to obtain fabric powder;
[0099] 2) taking 3 parts of the fabric powder obtained in step 1), firstly putting it into 96 parts of DMSO solvent, and carrying out the first stage stirring at 110° C., the stirring time is 1 hour, and the stirring speed is 300 r / min, so that the polyester is dissolved and the cellulose is swollen at the same time;
[0100] 3) adding LiCl to the mixed system obtained in step 2) so that the mass fraction of LiCl in the LiCl / DMSO ion solution system is 4%, continuing the second stage stirring at 110° C. for 1.5 h at a stirring speed of 100 r / min, then transferring the system to 50° C., and carrying out the third stage stirring under this condition for 1.5 h at a stirring speed of 50 r / min, to obtain a cellulose / polyester / LiCl / DMSO solution with uniform texture;
[0101] 4) The regenerated cellulose / polylactic acid composite fiber was obtained by dry-jet wet spinning. The spinning solution temperature was 100°C and the extrusion pressure was 3 kg / cm 2 , extrusion speed is 2m / min, spinneret diameter is 0.2μm, air gap is 1cm, coagulation bath is carried out in 35℃ deionized water; total draft multiple is 5 times, drying temperature is 50℃, winding speed is 10m / min.
[0102] Embodiment 19
[0103] The difference between Example 19 and Example 18 is that in step 3), after adding LiCl, the mass fraction of LiCl in the LiCl / DMSO ion solution system is 6%.
[0104] Embodiment 20
[0105] The difference between Example 20 and Example 18 is that in step 3), after adding LiCl, the mass fraction of LiCl in the LiCl / DMSO ion solution system is 8%.
[0106] Embodiment 21
[0107] The difference between Example 21 and Example 18 is that in step 3), after adding LiCl, the mass fraction of LiCl in the LiCl / DMSO ion solution system is 10%.
[0108] Embodiment 22
[0109] The difference between Example 22 and Example 21 is that step 2) is omitted, and 1 portion of fabric powder is directly added to the LiCl / DMSO ion solution system and stirred at high temperature for 2.5 hours.
[0110] The dissolution of the fiber in the cellulose / polyester / LiCl / DMSO solution obtained in step 3) is observed, as shown in Table 4. It can be seen from Table 4 that Examples 17 to 22 set different LiCl mass fractions, and the cellulose / polyester blended fabric can be dissolved into a uniform and stable solution within 4% to 10%. Example 22 is to directly mix the cellulose / polyester blended fabric with a mixed solvent system consisting of LiCl / solvent and stir it at high temperature and low temperature. The properties of the obtained solution are uniform and stable, which is almost the same as the solutions obtained in Examples 17 to 21. Example 17 is stirred at a low temperature of 30°C, and a uniform and well-dissolved solution can also be obtained. From the tensile performance data of the composite fiber obtained in step 4), it can be seen that with the increase of LiCl, the cellulose is dissolved more evenly, and the composite fiber obtained by spinning has higher performance.
[0111] Table 4 Dissolution and fiber properties of fabrics of Examples 17 to 22 after stirring in the third stage
[0112]
[0113] Comparative Example 1
[0114] The difference between Comparative Example 1 and Example 1 is that the stirring temperature in the first stage in step 2) and the second stage in step 3) is replaced with 70°C, and the step of switching to the third stage stirring at 40°C in step 3) is omitted.
[0115] Comparative Example 2
[0116] The difference between Comparative Example 2 and Example 1 is that the stirring temperature in the first stage of step 2) and the second stage of step 3) is replaced with 70°C.
[0117] Comparative Example 3
[0118] The difference between Comparative Example 3 and Example 1 is that the temperature of the third stage stirring in step 3) is replaced with 90°C.
[0119] Comparative Example 4
[0120] The difference between Comparative Example 4 and Example 3 is that the step of switching to the third stage of stirring at 30° C. in step 3) is omitted.
[0121] Comparative Example 5
[0122] The difference between Comparative Example 5 and Example 6 is that the stirring time in the second stage in step 3) is changed to 1 h.
[0123] Comparative Example 6
[0124] The difference between Comparative Example 6 and Example 15 is that the weight parts of the fabric powder in step 2) is changed to 11 parts.
[0125] Comparative Example 7
[0126] The difference between Comparative Example 7 and Example 17 is that in step 3), LiCl is not added during the second stage of stirring.
[0127] Comparative Example 8
[0128] The difference between Comparative Example 8 and Example 17 is that in step 3), after adding LiCl, the mass fraction of LiCl in the LiCl / DMSO ion solution system is 11%.
[0129] Table 5 Dissolution of the fabrics of Comparative Examples 1 to 8 and Examples 1, 3, 6, 15 and 17 after stirring in the third stage
[0130]
[0131]
[0132] The dissolution of the fiber in the cellulose / polyester / LiCl / solvent solution obtained in step 3) is observed, as shown in Table 5. It can be seen from Table 5 that the blended fabric cannot be completely dissolved only under high-temperature stirring conditions, as shown in Comparative Examples 3 and 4. It can be seen from the data of Example 1 and Comparative Example 3 that under high temperature conditions, even if the stirring time is long, the fiber cannot be completely dissolved, indicating that the dissolution of cellulose and polyester requires a combination of high-temperature stirring and melting and dissolving at a lower temperature. It can be seen from the experimental results of Example 1 and Comparative Examples 1-2 that when the temperature of high-temperature stirring is lower than 90°C, the fabric is difficult to swell completely, and even if a seemingly uniform solution is obtained after stirring, the solution will be stratified after standing. It can be seen from the experimental data of Example 6 and Comparative Example 5 that a shorter high-temperature melting and swelling time will also cause the fabric to be incompletely dissolved, and a mixed solution with a uniform texture after standing cannot be obtained, and subsequent spinning cannot be performed. It can be seen from the experimental data of Example 15 and Comparative Example 6 that too high a content of the blended fabric will cause the fabric to be unable to be completely dissolved. It can be seen from the experimental data of Example 17 and Comparative Examples 7-8 that the DMSO solvent alone in Comparative Example 7 cannot completely dissolve the cellulose / polyester fabric, and an excess of LiCl cannot completely dissolve the fabric either, and may even cause the solution to stratify after standing.
[0133] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing composite fibers by recycling cellulose / polyester blended fabrics by a one-bath process, characterized in that: The following steps are involved: (1) activating, washing and drying the cellulose / polyester blended fabric to obtain an activated blended fabric; (2) mixing the activated blended fabric obtained in step (1) with a solvent, and performing a first stage of stirring at a high temperature to dissolve the polyester component and simultaneously complete the swelling of the cellulose component; adding LiCl to the obtained mixed system to form a LiCl / solvent mixed solvent system with the solvent, and continuing to perform a second stage of stirring at a high temperature; (3) transferring the reaction system obtained in step (2) to a lower temperature environment and performing a third stage of stirring to complete the dissolution of the cellulose component and form a uniform mixed solution; (4) preparing composite fibers by a solution spinning process using the mixed solution obtained in step (3); Alternatively, (1) activating, washing and drying the cellulose / polyester blended fabric to obtain an activated blended fabric; (2) mixing the activated blended fabric obtained in step (1) with a LiCl / solvent mixed solvent system, and performing a first stage of stirring at a high temperature to dissolve the polyester component and simultaneously complete swelling of the cellulose component; and continuing to perform a second stage of stirring at a high temperature; (3) transferring the reaction system obtained in step (2) to a lower temperature environment and performing a third stage of stirring to complete the dissolution of the cellulose component and form a uniform mixed solution; (4) The mixed solution obtained in step (3) is subjected to a solution spinning process to prepare a regenerated composite fiber.
2. The method according to claim 1, characterized in that The cellulose / polyester blended fabric described in step (1) is a cellulose / polyester blended fabric or a cellulose / polylactic acid fiber blended fabric, and the mass fraction of cellulose in the cellulose / polyester blended fabric is 35-99%.
3. The method according to claim 1, characterized in that The activation described in step (1) refers to activation using a sodium hydroxide aqueous solution with a mass fraction of 5 to 20%, an activation temperature of 20 to 80° C., and an activation time of 1 to 5 hours.
4. The method according to claim 1, characterized in that The cleaning in step (1) refers to washing with deionized water and a solvent for 3 to 5 times respectively, wherein the solvent comprises at least one of DMF, DMAc and DMSO, the drying temperature is 40 to 50° C., and the drying time is 2 to 5 hours.
5. The method according to claim 1, characterized in that The solvent in step (2) comprises at least one of DMF, DMAc and DMSO, the mass ratio of the activated blended fabric to the LiCl / solvent mixed solvent system is 1 to 10:100, and the mass concentration of LiCl in the LiCl / solvent mixed solvent system is 2 to 10%.
6. The method according to claim 1, characterized in that The high temperature in step (2) is 90-150° C., the stirring speed is 30-600 r / min, the stirring time in the first stage is 1-2 h, and the stirring time in the second stage is 1-3 h.
7. The method according to claim 1, characterized in that In step (3), the relatively low temperature environment refers to an environment with a temperature of 20 to 60° C., the stirring time of the third stage is 1 to 3 hours, and the stirring speed is 30 to 600 r / min.
8. The method according to claim 1, characterized in that The spinning process described in step (4) refers to wet spinning or dry-jet wet spinning, and the breaking strength of the obtained regenerated composite fiber is 1.0-3.0 cN / dtex and the breaking elongation is 5-15%.
9. The method according to claim 1, characterized in that: In the solution spinning process of step (4), the temperature of the spinning solution is 80-120°C and the extrusion pressure is 1-5 kg / cm 2 , extrusion speed is 1-3m / min; spinneret diameter is 0.2μm, coagulation bath is carried out in deionized water at 20-40℃; air gap is 0-1cm, total draft multiple is 1-5 times, drying temperature is 30-50℃, winding speed is 1-15m / min.
10. The composite fiber prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method of using non-adhesive method to prepare cellulose base fiber
CN101550614A
Natural cellulose / polyacrylonitrile nano-antibacterial fiber membrane and preparation method thereof
CN104294479A
Non-polarized cotton cellulose / PVDF (polyvinylidene fluoride) composite piezoelectric fabric as well as preparation method and application thereof
CN116145304A